2020
DOI: 10.3390/ijerph17072470
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Human Resource Allocation Approach for Sustainable Traffic Management

Abstract: Efficient human resource deployment is one of the key aspects of road traffic management for maintaining the lifelines of any metropolitan city. The problem becomes relevant when collaboration between human resources with different skills in day-to-day operations is necessary to maintain public and commercial transport, manage various social events and emergency situations, and hence reduce congestion, injuries, emissions, etc. This study proposes a two-phase fuzzy multi-objective binary programming model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…However, it is worthy to note that there is poor literature on this field. Most of the optimisation fields related to the road management and maintenance problem are waste allocation problems [7]- [11], human resource allocation [12], allocating resources [13], [16], highway maintenance [14], [15], winter road maintenance [17], pavement and bridge maintenance [18]. TABLE 1 presents a summary of these most recent works.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worthy to note that there is poor literature on this field. Most of the optimisation fields related to the road management and maintenance problem are waste allocation problems [7]- [11], human resource allocation [12], allocating resources [13], [16], highway maintenance [14], [15], winter road maintenance [17], pavement and bridge maintenance [18]. TABLE 1 presents a summary of these most recent works.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Minimising the cost, CO2, staff personnel Maximising the segment allocation A two-phase fuzzy binary programming model Two-phase MIP programming method [12] Allocating resources to roadside incidents…”
Section: Multi-objective Nonlinear Programmingmentioning
confidence: 99%
“…Some research can be found in railway [19] and air traffic management [20] fields. The related areas in road traffic management are, for example, the allocation of human resources in sustainable traffic management to obtain a day-to-day manpower allocation schedule [21], emergency response resource allocation [22], and the mathematical model for efficiency optimization by determining the best number of employees for an logistics task [23]. Those studies have a common point; the right number of employees affects the effectiveness of a system.…”
Section: Introductionmentioning
confidence: 99%